SIFAT FISIS PAPAN SEMEN DARI LIMBAH KULIT BATANG SAGU - Rohny S. Maail (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
This research objectives were to investigate possibility of using the waste of sago cortex (Ela sagu/Wa’a) in the manufacture of cement board and to determine the physical properties of cement board based on the comparison in proportion of materials (cement, sago, water) and catalyst calcium chloride (CaCl2). Method were applied used completely randomesed design with tree replications in 3x3x3, with total 27 samples of cement board. The results shown that the waste of sago cortex ca be applied as raw materials to manufacture of cement board and fulfill the standard of particle board (JIS A 5908, 2003). The board have dencity which is almost equal to the target of dencity, lower value in water content, water absorption and thichness swelling so that have good performance in quality and stability dimensions. The sago cortex in side of base and the catalyst CaCl2 in 6% gave high performance for all physical properties of cement board.